The First Integral Method for the time fractional Kaup-Boussinesq System with time dependent coefficient - Kilic, Bulent; İnç, Mustafa (Elsevier Science Inc, 2015)
The first integral method (FIM) is applied to reach the different type solutions of the time fractional Kaup-Boussinesq (fKB) system with time dependent coefficient. It is obtained the envelope, bell shaped, triangular and kink soliton solutions of this equation. The method is an effective one to reach the different types of solutions of fractional nonlinear partial differential equations (fNPDE). (C) 2014 Elsevier Inc. All rights reserved.
Keywords: FIM; fKB equation; Time dependent coefficient